MORPHOMETRIC STUDY FOR IDENTIFICATION OF THE BACTROCERA DORSALIS COMPLEX (DIPTERA : TEPHRITIDAE) USING WING IMAGE ANALYSIS - A. ADSAVAKULCHAI'; V. BAIMAI; W. PRACHYABRUED; PAUL J. GROTE; S, LERTLUM (SEAMEO BIOTROP, 1999)
The Bactrocera dorsalis complex (Diptera: Tephritidae) used in this study included B. dorsalis, B. arecae, B. propinqua, B. pyrifoliae, B. verbascifoliae, and three new species complexes are species E, species K and species P. Bactrocera tau was used as an out-group. A total of 424 adults, which emerged from pupae collected from natural populations in Thailand, were prepared for wing measurements. Morphometric analysis was performed on measurements of wing vein characters. Wing images were captured in digital format and taken through digitalÂ image processing to calculate the Euclidean distance between wing vein junctions. Discriminant and cluster analyses were used for dichotomy of classification processes. All 424 wing specimens were classified to species in terms of the percentage of